THE INFORMATION ON STATUS OF ANTIBIOTIC RESISTANCE CHANGING THE PERCEPTION AND ATTITUDES OF WISELY ANTIBIOTIC USE IN BANYUMAS DISTRICT COMMUNITIES - Rahmawati Wulansari; Diyah Woro Dwi Lestari; Dwi Utami Anjarwati; Eman Sutrisna (Mandala Of Health, 2021)
The wise use of antibiotics in the Banyumas community is quite alarming. Most of them still buy antibiotics without a doctor's prescription, buy half a prescription and consume antibiotics without finishing it. Good enough knowledge about the dangers of using antibiotics unwisely has not formed a correct perception and attittude of antibiotic use. This study aims to evaluate changes in people's perceptions and attitudes about antibiotic use after being given information related to their resistance status . This research was conducted qualitatively on 10 informants. Retrieval of data through focus group discussion techniques is done before and after providing resistance status information. The results showed that before giving information, perceptions and attitudes towards the use of antibiotics most (80%) of informants were not correct despite having a good level of knowledge. Changes in perceptions and attitudes about the right pattern of antibiotic use wisely occur after being given information about the status of antibiotic resistance they experience. This study can be concluded that the provision of information on the results of the examination of resistance status has a positive effect causing the changing in perception and the right attitude regarding the use of antibiotics wisely in the Banyumas community